Activity of Aniline Methylation over Fe-Cu-Cr Ternary Spinel Systems - Reni George; Kochurani George; Sankaran Sugunan (Bulletin of Chemical Reaction Engineering & Catalysis, 2014)
A series of spinels having thegeneral formula CuCr2-xFexO4 with x=0.25,0.75, 1.25, 1.75 were prepared by co-precipitation method. The catalysts werecharacterized by various physico-chemical methods like XRD, BET, UV-DRS, SEM,EDX, TPD etc. The reaction of aniline with methanol was studied in a fixed-bedreactor system as a potential source for the production of various methylanilines. It was observed that systems possessing low ‘x’ values are highlyselective and active for N-monoalkylation of aniline leading toN-methylaniline. Reaction parameters were properly varied to optimize thereaction conditions for obtaining N-methylaniline selectively and in betteryield. Among the systems CuCr1.75Fe0.25O4 isremarkable due to its very high activity and excellent stability. Under theoptimized conditions N-methylaniline selectivity exceeded 91%. CuCr1.25Fe0.75O4gives better conversion than CuCr1.75Fe0.25O4in CuCr2-xFexO4 series. The Lewis acid sitesof the catalysts are mainly responsible for the good catalytic performance.  © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)